Walasuji Tradition in Bugis Tribe Traditional Weddings from an Islamic Law Perspective (Case Study in Solo Village, Bola District) - Abu Haif; Sulfiana Sulfiana; Ilfah Luthfiah; Hendri Hendri; Af Amul Khair (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study examines the Walasuji tradition, a part of the Bugis traditional wedding procession that still persists today. Walasuji is a rectangular woven basket filled with various fruits and foodstuffs, each with symbolic meaning. Etymologically, "wala" means to unite, while "suji" means to like or love wholeheartedly. The Bugis community believes this tradition is a symbol of household harmony and a means of social control to prevent divorce. The research results show that the Bugis community views the Walasuji tradition as an important part of the wedding procession, possessing not only aesthetic value but also educational, religious, and social significance. This tradition is believed to maintain household harmony and strengthen the value of siri' (family honor). From an Islamic legal perspective, Walasuji does not conflict with sharia because it is merely a cultural symbol that does not alter the substance of the marriage contract. However, if this tradition is made a requirement for a valid marriage, it is not in accordance with Islamic law. Therefore, Walasuji can be understood as a form of local wisdom that can be preserved as long as it complements the culture, not determines the validity of the marriage contract.